Hypnotic [videorecording (Blu-Ray)] - Rodriguez, Robert, 1968-; Borenstein, Max; Affleck, Ben, 1972-; Braga, Alice; Pardo, J. D.; Finley, Hala; Okeniyi, Dayo, 1988-; Fahey, Jeff; Haley, Jackie Earle, 1961-; Fichtner, William ([Relativity], 2024)
A detective becomes entangled in a mystery involving his missing daughter and a secret government program while investigating a series of strange, reality-bending crimes.